Pasta veloce : 100 fast and irresistible recipes from under the Tuscan sun - Mayes, Frances; Wyler, Susan (Abrams, 2023)
"Pasta Veloce offers a multitude of under-30-minute, luscious recipes, all accompanied by Mayes's evocative text. While there are numerous pasta cookbooks, few feature a true Italophile's passion and eye for detail that can get a dish to the table in, as Mayes describes, 'the time it takes to boil water.' From a Tagliatelle with Duck Confit, Chestnuts, and Coffee Reduction to a glittering Capellini with Golden Caviar to the perfect vodka sauce, Pasta Veloce is your guide on those nights when you're ready to skip the whole production of it but still want to eat like royalty in a rustic Italian village"--